Evaluasi Kesesuaian Desain Cerobong Blaze, Boiler, dan Genset terhadap Persyaratan Teknis Pengendalian Emisi di PT XYZ - Sugiharto, Arrantyo Ryan; Fadhil, Muhammad Faisal (Jurnal Serambi Engineering, 2026)
The animal feed industry emits air pollutants from combustion processes in blazes, boilers, and generators, which can harm the environment. Chimneys serve as the main control point to ensure these emissions are properly managed. Therefore, it is important to assess whether the chimney characteristics at PT. XYZ's blaze, boiler, and generator facilities comply with applicable environmental regulations. Field observations and Likert-scale assessments were carried out to evaluate chimney infrastructure and supporting facilities against the Decree of the Head of Bapedal No. 205 of 1996 and the Ministry of Environment and Forestry Regulation No. 11 of 2021. Parameters evaluated included chimney size, height, sampling point locations, and the presence of supporting facilities such as safety railings, ladders, working platforms, and electricity sources. Of the 18 chimneys examined, the average compliance level was 58% classified as “Fair”, with 7 chimneys rated “Good,” 5 rated “Fair,” 5 rated “Poor,” and 1 rated “Very Poor.” These results show that PT. XYZ has shown awareness by providing sampling facilities that meet technical standards, but remaining deficiencies reduce overall regulatory compliance. Recommended improvements include upgrading chimney facilities and infrastructure to enhance regulatory compliance and reduce operational risks during emission sampling.